THE STOCK PURCHASE STRATEGY DURING THE COVID-19 PANDEMIC - Teddy Hikmat Fauzi; Nurhayati Nurhayati; Andry Moch Ramdan; Muhammad Adnan Mushoddaq (Universitas Pasundan, 2022)
Since the COVID-19 pandemic throughout 2020, the Composite Stock Price Index (JCI) has decreased by minus 18.3% (idx.channel.okezone.com) and this is almost completely evenly distributed across several trading floors in the world. The urgency (priority) of this research is to be able to add a new perspective on the business environment analysis model as an investment strategy in determining and determining stock purchase decisions appropriately while considering internal and external business environmental factors that are able to dynamically influence investors' perceptions in minimizing losses on their portfolio of shares. This research method is a qualitative descriptive method. The key informants in this study were the manager of mutual securities in Bandung, the manager of UOB Kay Han Securities in the Bandung branch, and the manager of the securities in the Bandung branch. The Indonesia Stock Exchange (IDX) noted that the stock investor base, which incidentally is the millennial generation, has reached 60% of the total stock investors on the IDX. However, the results of a New Harris poll through the Stash application as quoted from the Financial Services Authority (OJK), almost 80% of young people do not even look at investing in the stock market. As many as 34% of the younger generation stated that they were reluctant to invest in stocks because the working system in the stock market was too difficult to learn or understand. Yes, you know, there are many terms in the capital market, especially stocks, such as bullish, bearish, and many others. Based on an interview with the Manager of Danareksa Sekuritas Branch Bandung as an informant, starting a stock investment is very easy. Capital for investment is currently starting from Rp. 100 thousand. No need to deposit millions of rupiah, just learn stock on the website, join trainings or enter capital market school. Self-taught learning can also be done by asking friends who have already entered the capital market or reading books and finding out on the internet. For stock investment, you must understand the basic knowledge first. Starting from learning to read the movement of the Composite Stock Price Index (JCI), when is the right time to buy or sell shares, to learning strategies and mitigating the risk of loss. To analyze and choose a strategy for buying shares during the COVID-19 pandemic, there are two basic approaches, namely : Fundamental Analysis Strategy and Technical Analysis Strategy.